MATHEMATICAL MODEL OF FOREST SUSTAINABILITY MANAGEMENT IN PERHUTANI BKPH BEGAL, KPH NGAWI, JAWA TIMUR - ADJI WARDANA (NIM : 10113064) , MHARTA
Forest Sustainability is one of the hydrological cycle supporting factor. Forest is said to be sustainable if there is appropriate composition of plant age class, age class of old plants tend to be more dominant than the age class of young plants. Old plants have strong roots and wide shade which able to inhibit the rate of soil erosion on the forest floor. In this study, we focused on the Perum Perhutani production plants, teak trees, which have age classes. Of course, to achieve the status of sustainable forest needs to do a good management of care and protection, therefore this research aims to predict the population dynamics of teak trees in order to determine relevant forest management policies and to find good strategy in maintaining forest conditions. In this research, we uses a mathematical model Leslie Matrices and Markov Chain. Leslie matrix is a matrix that contains entries of survival probability in its class and the probability to go up to the next class. At the end of this study, we get a conclusion that Ngawi Region Forest condition will recover to the expected time of Ã‚Â± 18 years. While the Markov Chain Model contain the state changes transition matrix, such as KU (Good) state, TBK (Poor) state and TK (Very Poor) state. Through analysis of the long-run behavior, we obtained the average period a class survive in its status according to the changes in forest which happen, so by simulate changes in forest conditions we get the areas of forest which is should be protected and preserved.